Global health leadership training in resource-limited settings: a collaborative approach by academic institutions and local health care programs in Uganda. Issue 1 (December 2015) - Nakanjako, Damalie; Namagala, Elizabeth; Semeere, Aggrey; Kigozi, Joanitor; Sempa, Joseph; Ddamulira, John; Katamba, Achilles; Biraro, Sam; Naikoba, Sarah; Mashalla, Yohana; Farquhar, Carey; Sewankambo, Nelson
Abstract Introduction Due to a limited health workforce, many health care providers in Africa must take on health leadership roles with minimal formal training in leadership. Hence, the need to equip health care providers with practical skills required to lead high-impact health care programs. In Uganda, the Afya Bora Global Health Leadership Fellowship is implemented through the Makerere University College of Health Sciences (MakCHS) and her partner institutions. Lessons learned from the program, presented in this paper, may guide development of in-service training opportunities to enhance leadership skills of health workers in resource-limited settings. Methods The Afya Bora Consortium, a consortium of four African and four U.S. academic institutions, offers 1-year global health leadership-training opportunities for nurses and doctors. Applications are received and vetted internationally by members of the consortium institutions in Botswana, Kenya, Tanzania, Uganda, and the USA. Fellows have 3 months of didactic modules and 9 months of mentored field attachment with 80% time dedicated to fellowship activities. Fellows' projects and experiences, documented during weekly mentor-fellow meetings and monthly mentoring team meetings, were compiled and analyzed manually using pre-determined themes to assess the effect of the program on fellows' daily leadership opportunities. Results Between January 2011 and January 2015, 15 Ugandan fellows (nine doctors and six nurses) participated in the program. Each fellow received 8 weeks of didactic modules held at one of the African partner institutions and three online modules to enhance fellows' foundation in leadership, communication, monitoring and evaluation, health informatics, research methodology, grant writing, implementation science, and responsible conduct of research. In addition, fellows embarked on innovative projects that covered a wide spectrum of global health challenges including critical analysis of policy formulation and review processes, bottlenecks in implementation of national HIV early infant diagnosis and prevention of mother-to-child HIV-transmission programs, and use of routine laboratory data about antibiotic resistance to guide updates of essential drug lists. Conclusion In-service leadership training was feasible, with ensured protected time for fellows to generate evidence-based solutions to challenges within their work environment. With structured mentorship, collaborative activities at academic institutions and local health care programs equipped health care providers with leadership skills.